Mainshock-aftersh​ock response analyses of FRP-jacketed columns in existing RC building frames. (15th June 2018) - Shin, Jiuk; Jeon, Jong-Su; Kim, JunHee
Highlights: Propose an innovative FRP-repair modeling scheme for shear-critical columns. Perform mainshock-aftershock response analyses. Investigate the effectiveness of FRP retrofit and repair schemes for an RC frame. Quantify the effect of mainshock responses upon aftershock responses for the FRP-retrofitted and repaired frames. Establish FRP retrofit and repair strategies to maximize the effectiveness of the FRP wrapping system. Abstract: Column jacketing techniques have been widely used to improve the seismic performance of existing reinforced concrete buildings and to mitigate additional damage induced by subsequent earthquakes to earthquake-damaged structures. To numerically assess damage mitigation of structures due to column jacketing under successive earthquakes, this study proposes a numerical modeling technique for shear-critical reinforced concrete columns retrofitted and repaired using fiber-reinforced polymer wraps and validates the simulated results with existing experimental data. A non-ductile reinforced concrete frame with the potential of column shear failure is then selected and modeled using the proposed modeling technique to evaluate the effect of FRP retrofit and repair upon mainshock and aftershock responses. In addition, two rehabilitation parameters such as story-related rehabilitation and number of FRP wraps are selected, and used to create rehabilitated frame models to maximize the effectiveness of FRP installations for the as-built frame under successive earthquakes. This effectiveness is examined in terms of the damage level of maximum and residual deformation.